2018
DOI: 10.18203/2349-3291.ijcp20183387
|View full text |Cite
|
Sign up to set email alerts
|

Study of morbidity and mortality profile in special care newborn unit at tertiary care teaching institute in Vadodara, Gujarat, India

Abstract: Background: The development of a country is defined by its healthcare status especially the maternal and child health. Neonatal Mortality Rate in India has always been an area of concern again due to logistic issues in implementation of preventive and curative programs in a large and diverse country as ours but has shown a slow but steady fall in the last 2 decades. The current NMR of Gujarat is 25.4/ 1000 live births (2016) which is similar to the national NMR. The goal is to bring down NMR to single digit. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
2
3
1
Order By: Relevance
“…Many previous have also observed perinatal asphyxia as the leading cause of death [15,16,22,23]. Pandya et al found sepsis as the common cause of death [24]. In contrast to this, there was no single death due to sepsis in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…Many previous have also observed perinatal asphyxia as the leading cause of death [15,16,22,23]. Pandya et al found sepsis as the common cause of death [24]. In contrast to this, there was no single death due to sepsis in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…This 10 Uttarakhand's study reported that major admission causes were jaundice, sepsis, and birth asphyxia, whereas birth asphyxia was the major cause of mortality, followed by sepsis and prematurity. Mortality was more in outborn babies, 14.67%, compared to inborn babies, 9.80%.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are variations between countries. Pandya et al have reported that sepsis contributed maximally to the mortality [16]. Similarly, the study report by the Indian Council of Medical Research also states sepsis to be the major cause of neonatal death [17].…”
Section: Discussionmentioning
confidence: 99%